ENVIAR: ENVIronment DAta SimulatoR - Almeida, Diego Rodrigues de; Machado, Patrícia D. L.; Andrade, Wilkerson L. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Context-aware applications (CAAs) sense and react to changes from the environment when performing their tasks. Testing such applications is challenging. Firstly, due to the number of combinations of possible events and values they can handle. Secondly, due to the different execution scenarios that may be hard to reproduce manually. We present the ENVIAR tool whose objective is to support test case generation and execution of Android CAAs. Generation combines a set of events that may trigger failure in such applications filtered by pairwise testing. Execution simulates the environment in which the CAA runs by sending mock data. Current version focus on Android events, GPS, and Internet sensor events and values. Empirical results have shown that the tool can generate test cases that detect context defects in real Android applications, particularly covering scenarios that would be tricky to run in a real environment.